2021
DOI: 10.21037/apm-21-286
|View full text |Cite
|
Sign up to set email alerts
|

Development of long-term cardiovascular disease risk prediction model for hemodialysis patients with end-stage renal disease based on nomogram

Abstract: Background: Chronic kidney disease (CKD) is a leading public health problem worldwide. Cardiovascular diseases are the primary cause of death in hemodialysis patients with CKD. Therefore, it is necessary to develop a simple risk assessment tool for cardiovascular events in hemodialysis patients with CKD.Methods: A cohort of 370 hemodialysis patients, who were recruited between January 2015 to September 2019 in south China, were involved in the present study. On the basis of routine blood test indicators and ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…Li et al [ 8 ] showed that the nomogram model predicted the probability of withdrawal in peritoneal dialysis patients. In addition, You et al [ 9 ] developed a simple and practical nomogram prediction model that could assess the risk of cardiovascular events in long-term hemodialysis patients with chronic kidney disease. However, there is no accurate nomogram model to assess the risk factors for cardiovascular events in DN patients receiving maintenance hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 8 ] showed that the nomogram model predicted the probability of withdrawal in peritoneal dialysis patients. In addition, You et al [ 9 ] developed a simple and practical nomogram prediction model that could assess the risk of cardiovascular events in long-term hemodialysis patients with chronic kidney disease. However, there is no accurate nomogram model to assess the risk factors for cardiovascular events in DN patients receiving maintenance hemodialysis.…”
Section: Introductionmentioning
confidence: 99%
“…After reviewing the titles and abstracts, 3224 articles were excluded, leaving 86 articles to be read in full text. Ultimately, nine articles [14][15][16][17][18][19][20][21][22] containing 12 models were included (Figure 1). indicates not mentioned.…”
Section: Data Search and Included Literaturementioning
confidence: 99%
“…Three prospective cohort studies 14,17,19 and six retrospective cohort studies 15,16,18,[20][21][22] were included in the nine articles. The total sample size comprised 16,529 patients, with 3651 patients experiencing an outcome event.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, the establishment of an effective prediction model by combing multiple prognostic factors could play an important role in clinical risk assessment and individual patient’s treatment [ 11 ]. There have been few studies based on the biochemical indicators of liver and kidney function needed to construct a prediction model associated with the risk of ESRD patients receiving HD [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%